A different man [videorecording (Blu-Ray)] - Schimberg, Aaron; Schimberg, Aaron; Schimberg, Aaron; Smerilli, Umberto; Levi, Taylor; Garfield, Wyatt; Arancio, Lawrence; Davidson, Neal (Actor); Griffith, Billy; Jackson, Miles G.; Pearson, Adam, 1984-; Reinsve, Renate; et al. (A24, 2024)
Aspiring actor Edward undergoes a radical medical procedure to drastically transform his appearance. But his new dream face quickly turns into a nightmare, as he loses out on the role he was born to play and becomes obsessed with reclaiming what was lost.